The Study on the Application of the OBE Concept in Comprehensive English Teaching - Wang, Shengliang (Pacific International Journal, 2024)
This thesis explores the implementation of Outcomes-Based Education (OBE) in comprehensive English teaching in higher education. Emphasizing a student-centered approach, the OBE concept focuses on achieving specific outcomes, personalized assessments, practical application of knowledge, and adaptability for future life. The study identifies issues in traditional English teaching, such as a focus on test-taking over practical skills and outdated teaching models. Integrating OBE addresses these issues by enhancing language application, improving teaching quality, and creating more learning opportunities. The proposed teaching model under the OBE concept includes setting course objectives, designing aligned teaching content, and evaluating learning outcomes through formative and summative assessments. The thesis also discusses challenges in applying the OBE concept and suggests solutions like establishing OBE promotion organizations, providing relevant training, enhancing inter-university communication, and improving feedback mechanisms.